2010
DOI: 10.1111/j.1349-7006.2010.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Mus81 as a novel prognostic biomarker for patients with colorectal carcinoma

Abstract: The Mus81 gene encodes a critical endonuclease involved in DNA repair and tumor suppression. Our previous study has shown reduced expression of Mus81 in hepatocellular carcinoma and its association with the metastastic potential and prognosis of hepatocellular carcinoma. However, the role of Mus81 in colorectal carcinoma is currently unknown. We therefore carried out the present study to explore the correlation between Mus81 expression and the progression of colorectal carcinoma. Mus81 expression in 92 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
3
29
1
Order By: Relevance
“…Nonetheless, these mutants exhibit mitotic defects and are hypersensitive to specific DNA-damaging agents, including CPT, cisplatin, and MMC. The observation that MUS81 is down-regulated in hepatocellular and colon carcinoma provides circumstantial evidence that MUS81-EME1 is also required for chromosomal stability in humans (Wu et al 2008(Wu et al , 2011.…”
Section: Canonical Nuclear Hj Resolvases: Gen1/yen1mentioning
confidence: 94%
“…Nonetheless, these mutants exhibit mitotic defects and are hypersensitive to specific DNA-damaging agents, including CPT, cisplatin, and MMC. The observation that MUS81 is down-regulated in hepatocellular and colon carcinoma provides circumstantial evidence that MUS81-EME1 is also required for chromosomal stability in humans (Wu et al 2008(Wu et al , 2011.…”
Section: Canonical Nuclear Hj Resolvases: Gen1/yen1mentioning
confidence: 94%
“…EGFL6 is overexpressed in benign meningioma tissues and serum (16). Downregulation of EGFL8 expression has been observed in gastric cancer, and is significantly correlated with high tumor-node-metastasis stage and poor prognosis in gastric and colorectal cancer (17,18). Recent studies by our group have demonstrated that EGFL8 has inhibitory effects on mouse thymic epithelial cells and thymocytes, indicating that it is a negative regulatory molecule in T-cell development in the mouse thymus (19,20).…”
Section: Molecular Characterization and Expression Analysis Of Mouse mentioning
confidence: 99%
“…First-strand cDNA was obtained via reverse transcription using 2 µg total RNA. The reaction was performed in 20 µl buffer containing 0.5 µg oligo(dT) [12][13][14][15][16][17][18] primer, 50 mM Tris-HCl (pH 8.3), 75 mM KCl, 3 mM MgCl 2 , 40 mM dithiothreitol, 0.5 mM deoxynucleotide triphosphate mixture, 10 units RNase inhibitor and 200 units Moloney murine leukemia virus reverse transcriptase (all from Invitrogen Life Technologies). After incubation at 37˚C for 60 min, the reaction was stopped via heating at 70˚C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The activation of oncogenes such as the ras gene and the inactivation of tumor suppressors such as adenomatous polyposis coli and p53 genes have been well documented in CRC (4)(5)(6). In addition, we previously identified certain genetic changes, including the downregulation of MUS81 structure-specific endonuclease subunit and epidermal growth factor-like protein 8 precursor, to be associated with this malignancy (7,8). However, further investigations are still necessary to clarify the tumorigenic pathway of CRC (9).…”
Section: Introductionmentioning
confidence: 99%